Examining the interplay between positive and negative bureaucracy characteristics and job satisfaction - Barbara Barbieri; Diego Bellini; Giuseppe Scaratti; Marina Mondo; Roberta Pinna; Maura Galletta; Silvia De Simone (Akademisk Kvarter)
Traditionally, literature considers public administration as a bureaucratic institution where managers and employees must adhere to rigid structures and procedures. However, a bureaucratic organizational culture can either support employees (e.g., enabling practices) or conversely exerts control (e.g., coercive practices), thus influencing various psychosocial and organizational outcomes, including job satisfaction. Despite the well-recognized features of this bureaucratic structure, few studies have examined its dual effect on job satisfaction. A cross-sectional study was conducted with a sample of 414 managers in the public sector. The results of the hierarchical regression analysis revealed that enabling bureaucracy positively affects job satisfaction, while coercive bureaucracy has a significant and negative impact on job satisfaction. Furthermore, resistance to change moderates the impact of bureaucracy’s coercive aspects on job satisfaction.